ANALISIS PEMANFAATAN LIMBAH TANDAN KOSONG KELAPA SAWIT SEBAGAI PUPUK BAGI MASYARAKAT SIMANDIANGIN KAB. LABUHANBATU SELATAN - Mahira Azura Putri; Serly Dinda Afriwana, Syariah Hilaliyah Pulungan, Abdurrozzaq Hasibuan (CV. ADIBA AISHA AMIRA, 2024)
EFB (Empty Palm Oil Bunches) is waste that is produced in large quantities by palm oil mills in Indonesia. About 22-23% OPEFB is produced from every ton of FFB (Fresh Fruit Bunches), or around 220-230 kg of OPEFB. Unfortunately, most of the palm oil mills and communities in Indonesia have not fully utilized this waste. The problem in this research is how to use empty oil palm bunches as organic fertilizer for the people in Simandiangin Village, Kab. South Labuhanbatu. The research method uses qualitative methods by going directly to the field and using interview techniques. The results of research in the village of Simandiangin, Kab. Labuhanbatu Selatan found that the empty fruit bunches were bought from the factory using a truck and piled into the area closest to the tree to be fertilized. Within a year the owners of oil palm plantations in this area buy about 2 times a year. Then the owner of the garden employs several people to directly arrange them in a circle to the oil palm plants. In the application of empty fruit bunches, approximately 20-30 empty fruit bunches for oil palm plantations are given. The conclusion in this study is that the use of empty fruit bunches as organic fertilizer has considerable potential to help increase soil fertility and agricultural productivity. Oil Palm Empty Bunches (EFB) can be used as mulch, namely the covering layer of soil around the plants. The purpose of mulch is to reduce water evaporation, retain soil moisture, and inhibit weed growth. In addition, empty bunches will also decompose over time and provide nutrients to the plants